A MODEL FOR THE DEVELOPMENT OF STUDENT SELF-LEARNING COMPETENCIES IN A CREDIT-MODULE SYSTEM - Xomidjonovna, Boltaeva Barnoxon; Botirovna, Sultanova Lola (PT. Antis International Publisher, 2024)
The article makes an attempt to analyze the problems of organizing independent work of students in modern learning conditions and identifies the prospects for work to improve its effectiveness in the conditions of a credit-modular education system. The credit-module organization of the learning process ensures the psychological development of the relationship between teacher and student. These relationships contribute to the development of general educational skills and abilities, in addition, the independence of students in the educational process.